The Influence of Store Atmosphere and Product Assortment on Repurchase Intention with Customer Satisfaction as a Mediating Variable at MR. DIY Kayu Merah - Mutmainah, Mutmainah; Fahri, Johan; Buamonabot, Irfandi (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the influence of store atmosphere and product assortment on repurchase intention with customer satisfaction as a mediating variable among customers of MR. DIY Kayu Merah, Ternate. The study used a quantitative approach, with a purposive sampling method targeting 150 customers who had made at least three purchases. The data was collected through questionnaires and analyzed using the SEM-PLS method with SmartPLS 4.0 software. The results indicate that store atmosphere positively influences both customer satisfaction and repurchase intention. Meanwhile, product assortment significantly affects customer satisfaction but not repurchase intention directly. Furthermore, customer satisfaction positively impacts repurchase intention and mediates the relationship between both store atmosphere and product assortment with repurchase intention.